2018
DOI: 10.1017/s0021932018000214
|View full text |Cite
|
Sign up to set email alerts
|

Differentials in Sexual and Reproductive Health Knowledge Among East Malaysian Adolescents

Abstract: SummaryThe aim of this study was to assess the knowledge of East Malaysian adolescents on sexual and reproductive health issues. Data were collected in March-July 2015 from 2858 adolescents aged 13-18 years from selected East Malaysian secondary schools using a self-administered questionnaire. Twelve items relating to sexual and reproductive health were used to measure respondents' knowledge based on their responses 'True', 'False' or 'Don't know', with the proportion of correct answers being the variable of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A recent study conducted among Malaysian schoolgirls also claims that girls’ place of living and age are associated with their level of sexual and reproductive health knowledge. Older girls and those from urban schools are reported to have significantly higher levels of knowledge than younger girls and those from rural schools (Awang et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted among Malaysian schoolgirls also claims that girls’ place of living and age are associated with their level of sexual and reproductive health knowledge. Older girls and those from urban schools are reported to have significantly higher levels of knowledge than younger girls and those from rural schools (Awang et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For each item, respondents were required to select one option from the following: “True”, “False”, or “Don’t Know”. The number of correct answers for each item in this study represented SRH knowledge score [ 29 ]. With the median split method, the cut-off point of eight was used to categorise the level of SRH knowledge into “poor” and “good”.…”
Section: Methodsmentioning
confidence: 99%
“…Globally, 15 million women below the age of 20 had become mothers, comprising up to one fifth of the total population of women who have given birth, and each year, a substantial number of these women developed complications due to pregnancy and other birth-related illnesses (4). Studies also showed that adolescents were at higher risk of being infected with sexually transmitted diseases (5), developed undesirable pregnancy outcomes when pregnant and were commonly involved in unsatisfactory or forced early sexual relationships (6,7). Though it is apparent that not every pregnancy during adolescence results in obstetric complications, early adolescent pregnancies ought to be reduced using effective programs and strategies (8).…”
Section: Introductionmentioning
confidence: 99%